2
$\begingroup$

$$ \log_{3x+7}{(9+12x+4x^2)}+ \log_{2x+3}{(6x^2+23x+21)} \ge 4$$ The logarithmic inequality is defined for: $ x \in (-3/2, -1) \cup(-1, \infty)$.

First, I supposed that my solutions are in the interval $(-3/2, -1)$. Following this interval for which the logarithmic function $t$ are decreasing and multiplying both sides of the inequality by $\log_{2x+3}{(3x+7)}$, I obtained: $$ 2+ [1+\log_{2x+3}{(3x+7)}-\log_{2x+3}{6}]\cdot\log_{2x+3}{(3x+7)} \le4\log_{2x+3}{(3x+7)}\\ \log_{2x+3}{(3x+7)}=t<0\\t^2-(3+\log_{2x+3}{6})t+2 \le0$$ And here I got stuck. This inequailty is intended to be solved witouth a calculator, is it possible to continuie doing the inequality withouth it? And what I did wrong?

$\endgroup$
2
$\begingroup$

Hint:

$$9+12x+4x^2=(2x+3)^2$$

$$ 6x^2+23x+21=(2x+3)(3x+7)$$

$$4\le\log_{3x+7}(2x+3)^2+\log_{2x+3}(2x+3)(3x+7)=2\log_{3x+7}(2x+3)+1+\log_{2x+3}(3x+7)$$

As $\log(y)$ is real for $y>0,$

we need $2x+3, 3x+7>0\implies x>$max$(-3/2,-7/3)=-3/2$

Now if $\log_{3x+7}(2x+3)=a,$

$$4\le2a+1+\dfrac1a$$

$$\iff0\le2a+\dfrac1a-3=\dfrac{2a^2-3a+1}a=\dfrac{(2a-1)(a-1)}a$$

If $\dfrac{(2a-1)(a-1)}a=0, a=1$ or $\dfrac12$

Else we need $a(2a-1)(a-1)>0$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.